NILAI HUMOR URANG BANJAR DALAM KISAH HIDUP SUMAMBING - Juhaidi, Ahmad (Pascasarjana UIN ANTASARI Banjarmasin, 2009)
This paper explores the life stories of Sumambing Kandangan, Hulu Sungai Selatan. Stories of life Sumambing in this paper are grouped into eschew attitude in the sense of guilt and shame, simple and silly, and not ill-natured. Values of real stories of Sumambing are: (1) Acts Sumambing humor is a story of resistance to become a porno movie urang Banjar stigma; (2)patienty; (3) naughtiness does not have to be faced with anger because the anger that is the the goal naughties; (4) recognize the error. Errors should not be hidden but the climb will show greatness of the soul; and (5) resistance to general public attitudes. Sumambing show the attitude of the people that society in general does not always have to be a precedent and followed.